PRODUKSI DAN PEMASARAN KOPI-PRO DENGAN PENAMBAHAN PROBIOTIK ASLI INDONESIA SEBAGAI ALTERNATIF MINUMAN SEHAT: PRODUCTION AND MARKETING OF COFFEE-PRO WITH THE ADDITION OF - Sefni Hendris; Feliatra feli; Adelina; Asmika H Simarmata; Rizki Oktavian; Nabila Afifah Azuga (LPPM Universitas Abdurrab, 2025)
Coffee is one of the commodities with high economic value and is widely favored by the public. Innovation in coffee processing through the addition of probiotics offers an opportunity to produce functional products that not only have nutritional value but also business potential. This community service activity aims to enhance students’ competence in entrepreneurship based on the innovation of probiotic coffee beverages (Kopi-Pro) by utilizing the Bacillus cereus SN7 consortium as a source of single-cell protein. The implementation methods include socialization, training, mentoring, as well as monitoring and evaluation. Organoleptic tests on the aroma and taste of robusta coffee showed that the treatment with the highest probiotic dosage, 4% (treatment D), received the highest preference score from the panelists. Marketing trials conducted in three PKKMB events resulted in all products being sold out with a total revenue of IDR 1,682,000, supported by a 65% repeat purchase interest rate, indicating a positive consumer response. These results confirm that Kopi-Pro has the potential to be developed as a probiotic-based functional beverage with economic value and can serve as a student entrepreneurship model after graduation.